2013
DOI: 10.2174/1570162x11311030007
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Depression and its Correlation with Serum Carnitine Level in HIV/AIDS Patients

Abstract: There are some evidences regarding beneficial effects of carnitine in improvement of depression symptoms. Incidence of depression is significantly higher among HIV positive individuals compared to HIV negative populations. Also carnitine deficiency is prevalent in HIV positive individuals. In a cross-sectional study correlation between serum carnitine level and depression severity based on the Beck Depression Inventory questionnaire was assessed in 100 HIV/AIDS (42 males and 58 females) patients. According to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Cassol et al ( 45 ) found decreased monoamine metabolites (phenylacetate, 4-hydroxyphenylacetate) and ACs (C3:0, iso C4:0, iso C5:0, 2-methyl C4:0) in plasma distinguished depressed subjects from controls in HIV-positive and HIV-negative cohorts, and these alterations were correlated with the severity of depression. However, a study showed that no significant correlation was found between depression and serum carnitine level as well as dietary carnitine intake ( 46 ). In view of the conflicting results presented above, future research should be conducted in larger samples.…”
Section: Carnitine and Depressionmentioning
confidence: 99%
“…Cassol et al ( 45 ) found decreased monoamine metabolites (phenylacetate, 4-hydroxyphenylacetate) and ACs (C3:0, iso C4:0, iso C5:0, 2-methyl C4:0) in plasma distinguished depressed subjects from controls in HIV-positive and HIV-negative cohorts, and these alterations were correlated with the severity of depression. However, a study showed that no significant correlation was found between depression and serum carnitine level as well as dietary carnitine intake ( 46 ). In view of the conflicting results presented above, future research should be conducted in larger samples.…”
Section: Carnitine and Depressionmentioning
confidence: 99%
“…In this systematic review, 591 cross-sectional studies were included, 483 from international databases, 77 from national databases, and 30 from the reference lists of the selected studies, and 1 through contacting the authors. Finally, after removing duplicated studies and checking the eligibility criteria, 9 cross-sectional studies ( 13 , 18 - 22 , 27 - 29 ) were included in the review ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…To date, several cross-sectional studies have estimated the prevalence of depression among these patients. According to the results of these studies, the prevalence of depression has been reported to be 53% to 85% ( 13 , 18 - 22 ), therefore, there is no universal consensus about the prevalence of depression among these patients in Iran. This systematic review aimed at estimating the overall prevalence of depression among Iranian patients with HIV and AIDS.…”
Section: Introductionmentioning
confidence: 99%
“…Failure to adjust can in turn lead to clinical depression, anxiety, stress, and poor coping (Vanable 2006). Particularly, the prevalence of depression and suicide in people living with HIV/AIDS is very high (Cooperman 2005; Rezaee 2013; Bhatia 2014; Anagnostopoulos 2015). …”
Section: Introductionmentioning
confidence: 99%